Understanding collaboration in short food supply chains: a focus on collaborative relationships, interaction mechanisms and relational benefits - S. Stoeva; R. Van Gompel; L. Van den Bossche; E. Rogge; P. Slavova; M. Grivins; I. Mileiko (Agricultural and Food Economics)
Abstract The article provides an original conceptual framework to advance the knowledge of short food supply chains (SFSCs) collaboration by bridging supply chain management approaches with empirical evidence from the agri-food sector. Through an in-depth analysis of 14 initiatives across Europe, it explores the multi-faceted nature of SFSCs collaboration, revealing a complex interplay between collaborative relationships, interaction mechanisms, and relational benefits. By identifying seven key interaction mechanisms—information sharing, decision synchronisation, goal congruence, incentive alignment, resource sharing, joint knowledge creation, and collaborative communication—the article shows how these mechanisms generate both tangible and intangible relational benefits, including fair pricing, reduced transaction costs, enhanced market knowledge, technological skills, and stronger community engagement. The findings demonstrate that SFSCs collaborations operate as dynamic ecosystems characterised by complex interdependencies among diverse actors. This diversity extends beyond traditional business-to-business (B2B) models to include business-to-consumer (B2C), consumer-to-business (C2B), and hybrid business-to-business-to-consumer (B2B2C) relationships. These varied collaborative structures facilitate mutual learning, innovation, and value co-creation, crucial for the resilience and adaptability of local food systems. The presence of robust interaction mechanisms is essential for fostering effective partnerships and generating relational benefits, even if not all mechanisms are consistently present in every type of collaborative relationships.